2021
DOI: 10.26858/ijole.v5i4.22495
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Approach in Online EFL Class Using Islamic Learning Materials: Students' Perspective

Abstract: This study aims to find out how students' perspectives on learning English use 21st century learning strategies through a multimodal approach to teaching English for EFL students. A lecture was conducted online for one semester (four months) by using Islamic topics as learning materials. The learning materials were presented and discussed, then students were asked to write or talk about the topics. This study uses a descriptive qualitative approach to data collection through the provision of questionnaires and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
(66 reference statements)
0
6
0
1
Order By: Relevance
“…The study discovered that multimodal composing increased EFL learners' English overall writing performance. It is also supported by Djamdjuri et al (2021) who found that multimodal activities helped students to improve their English language skills and get a lot of students' interests. Another research by Jiang & Luk (2016) highlighted that the students were interested in multimodal composing as a result of the challenge, curiosity, control, collaboration, competitiveness, and recognition that they experienced following the implementation of multimodal composing in their classroom.…”
Section: Introductionmentioning
confidence: 84%
“…The study discovered that multimodal composing increased EFL learners' English overall writing performance. It is also supported by Djamdjuri et al (2021) who found that multimodal activities helped students to improve their English language skills and get a lot of students' interests. Another research by Jiang & Luk (2016) highlighted that the students were interested in multimodal composing as a result of the challenge, curiosity, control, collaboration, competitiveness, and recognition that they experienced following the implementation of multimodal composing in their classroom.…”
Section: Introductionmentioning
confidence: 84%
“…must constantly accommodate technical changes to attempts to improve educational quality, particularly in the use of information and communication technology for the world of education, particularly in the learning process (Djamdjuri, Suseno, Tajuddin, Lustyantie, & Chaeruman, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The rapid development of information technology in the current era of globalization is inevitable its influence on the world of Education (Komalasari, 2020).. The global era requires the world of education to always and always adjust technological developments to efforts in improving the quality of education, especially adjusting the use of information and communication technology for the world of education, especially in the learning process (Djamdjuri, Suseno, Tajuddin, Lustyantie, & Chaeruman, 2021). Therefore, this study intends to explore how integration technology affects students' attitudes during distance learning that is taking place due to the Covid-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Multimodal is a term that is used to refer to the way people communicate using different modes at the same time (Kress & van Leeuwen, 1996), which is defined as the use of several semiotic methods in product design, or semiotic events simultaneously, and in a certain way these modes combined with strengthening, compliment, or be in a certain arrangement (Kress and van Leeuwen, 2001), according to (Al Fajri, 2018). Multimodal learning refers to an embodied learning situation involving multiple sensory systems and learner action systems (Lustyantie & Arung, 2020; Massaro, 2012), according to (Djamdjuri et al, 2021). This phenomenon of multimodality is not new.…”
Section: Multimodal Discourse Analysismentioning
confidence: 99%